Effects of Durian Intake on Blood Pressure and Heart Rate in Healthy Individuals. Issue 7 (2nd July 2016) - Kumolosasi, Endang; Siew Gyn, Teh; Mansor, Ahmad Hasnan; Makmor Bakry, Mohd; Azmi, Norazrina; Jasamai, Malina
Abstract : The effect of durian on cardiovascular health remains controversial. This study investigated the correlation between durian intake and the elevation of blood pressure and heart rate in healthy males. Subjects consumed either placebo, 250 or 500 g durian flesh. The blood pressure and heart rate were measured at various intervals up to 24 h. Both systolic and diastolic blood pressure remained normal for groups given durian. However, a significant increase in heart rate was observed in the group given 500 g of durian at 0.5–2 h. A modest amount of durian intake did not affect blood pressure and heart rate in healthy individuals.